The Jews of Eastern Europe, 1772-1881 - Barṭal, Yiśraʼel (Jewish culture and contexts., 2005)
In the nineteenth century, the largest Jewish community the modern world had known lived in hundreds of towns and shtetls in the territory between the Prussian border of Poland and the Ukrainian coast of the Black Sea. The period had started with the partition of Poland and the absorption of its territories into the Russian and Austro-Hungarian empires; it would end with the first large-scale outbreaks of anti-Semitic violence and the imposition in Russia of strong anti-Semitic legislation. In the years between, a traditional society accustomed to an autonomous way of life would be transformed into one much more open to its surrounding cultures, yet much more confident of its own nationalist identity. InThe Jews of Eastern Europe, Israel Bartal traces this transformation and finds in it the roots of Jewish modernity.